Design and development of automatic warehouse sorting rover. (2021) - Subrahmanyam, R.V.; Kiran Kumar, M.; Nair, Suraj; Warrier, Sagar; Prashanth, B.N.
Abstract: These days the importance of automation has been increasing drastically; time consumption is also one of the most important factors that affects the productivity. The other factors that should be considered are less human effort, reduced lead time, elimination of work force from unproductive jobs, clear and hassle-free system. In most of the electronic commerce companies like Flipkart, Amazon, Myntra etc., the sorting of different type of products happens based on the customer orders. It becomes a huge problem for selecting an item from a very big warehouse. There are already many such kind of sorting system that are present in most of the companies but the main drawback is that, the existing systems are not so efficient and appropriate in the sorting mechanism. Above being the case, the project deals with improving the sorting system in more appropriate and efficient approach. In current scenario, the sorting is done by a rover and is completely programmed. When the order is placed by the customer, the rover gets the signal, i.e., location of the object or the rack position, where the product is present in the warehouse. The rover moves to the required location and gets the entire rack to the labelling counter. In the labelling counter, the operator picks the required object and leaves the rest, then again, the robot places back the entire rack to the previous location, as a result, there will be a lot and lots of loss in time and power. Above being the case, the warehouse sorting is modified in such a way that the above-mentioned problems will be resolved. The objective is to redesign both the rover and the rack in order to sort the items with ease and efficient. The rover is completely automated, the user simply need to give the initial location and the final destination of the product to sort. Rover is programmed to reach the required location of the rack. The specified items are placed onto the rover and it will bring the specified object to the labeling counter. On the other hand, rack is designed depending upon the dimensions of the object and the purpose. A mechanism is developed for rack to place a required object onto the rover. This will simplify the process so that the operator need not have to search the product from the entire rack.